Knowledge, attitude and practice regarding menstrual hygiene among secondary level students - Mina Paudel,; Richa Ray,; Mala Rijal,; Tanuja Chaudhary, (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Menstrual hygiene is an integral aspect of health and wellbeing of adolescent girls. However, effective management to improve menstrual health remain scarce which is evidence by widespread lack of knowledge and unhealthy practice. The objective of this study was to find out knowledge, attitude and practice related to menstrual hygiene among secondary level students in Janakpur, Nepal.Materials and Methods: A cross-sectional descriptive study design was used   in secondary level girls of Shree Laxminiya Janata Secondary School of Dhanusha district studying in grade 9,10,11, & 12. A self -administered structured questionnaire was used to collect data by using total enumerative method. All together 210 students are taking part and entire students fill the form.   Descriptive (frequency, percentage, mean and standard deviation) and inferential statistics (chi-square test) was used.Results: The study revealed that 52.86%of the respondents had good level of knowledge regarding menstrual hygiene. It also showed that 53.33% had favorable attitude regarding menstrual hygiene. Similarly, 54.77% of the respondents had good practice regarding menstrual hygiene. Family income p=0.001), grade (p=0.03), age (p=0.007), mother education status (p= 0.003), family occupation (p=0.001), family income (p=0.012) was statistically significant with level of knowledge, and attitude regarding menstrual hygiene. There was statistically significant between level of practice regarding menstrual hygiene and grade (p=0.002) and family income (p=0.004). There was also statistically significant association between respondent knowledge and practice p=0.045 and also statistically significant association between respondent knowledge and attitude p=0.0002.Conclusion: Significant portion of students demonstrated a good understanding of menstrual hygiene, some still lack sufficient knowledge, although their practice is not poor. It is recommended that concerned authority to conduct awareness program regarding menstrual hygiene so that it helps to generate knowledge.